Cloud management and security - Abbadi, Imad M. (John Wiley & Sons Inc., 2014)
"This book discusses the foundations of Cloud computing, and covers in detail two main aspects of Cloud computing"- Resumé vydavatel
Keywords: cloud computing; WWW služby; počítačová bezpečnost; web services; computer security; monografie; elektronické knihy; monographs; electronic books